The development of the wide-range 4D appearance function for breakage characterisation in grinding mills. (15th August 2017) - Yu, P.; Xie, W.; Liu, L.X.; Powell, M.S.
Graphical abstract: Highlights: Two wide-range 4D (four dimensional) appearance function models were developed. The P80-m-q based 4D model predicts best compared with other models. The 4D models are more accurate and scalable than existing models. The 4D models extend the size range to −63 + 0.425 mm with wider applicable scopes. Abstract: The Appearance function, also known as breakage distribution function, is used to describe the breakage characteristics of an ore impacted with a certain energy. It is the bedrock of comminution modelling. The range of applicability of the majority of existing appearance functions is limited to coarser sizes above a few millimetres. In the previous work, a 4D (four dimensional) appearance function model was developed based on JKRBT test data, but its applicable range was not sufficiently broad at −24.4 + 7.3 mm. In order to develop a more versatile appearance function model that can be used for a wide range of energy levels and feed particle sizes, drop weight tests for smaller particles with sizes ranging from 425 μm to 16 mm were carried out with the Mini JK drop weight tester. Combined with data up to 63 mm from Standard JK Drop Weight Tests, the outcomes were fitted to two types of 4D appearance functions - the P80-m based 4D model and the P80-m-q based 4D model. The proposed 4D models are more accurate and scalable than existing models. Most importantly, they can be used for a wide range of conditions, with feed particle size ranging from 425 μm to 63 mm and input specific energy from 0.1 to 2.5 kW h/t in the initial test data.